2019
DOI: 10.1101/699561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterising the mechanisms underlying genetic resistance to amoebic gill disease in Atlantic salmon using RNA sequencing

Abstract: ABSTRACTBackgroundGill health is one of the main concerns for Atlantic salmon aquaculture, and Amoebic Gill Disease (AGD), attributable to infection by the amoeba Neoparamoeba perurans, is a frequent cause of morbidity. In the absence of preventive measures, increasing genetic resistance of salmon to AGD via selective breeding can reduce the incidence of the disease and mitigate gill damage. Understanding the mechani… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Farming in net pens is typically associated with the multifactorial gill diseases (PGD, PGI or CGD) rather than the single-cause gill pathologies, such as AGD (Herrero et al, 2018;Gjessing et al, 2019;Laurin et al, 2019). So far, the extensive transcriptomic profiling of the gill tissue has been performed only in salmon exposed to the controlled environment of the closed-system tanks, following a single-pathogen challenge to induce either AGD (Morrison et al, 2006;Wynne et al, 2008a;Bloecher et al, 2018;Boison et al, 2019;Robledo et al, 2019) or infectious salmon anemia (Valenzuela-Miranda et al, 2015). In most cases, fish were subjected to a single-dose challenge of the infectious organisms, with only few studies evaluating the effects of re-infection (Bloecher et al, 2018;Boison et al, 2019) or co-exposure to other infectious agents, such as hydroids (Bloecher et al, 2018) and Yersinia ruckeri (Valdenegro-Vega et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Farming in net pens is typically associated with the multifactorial gill diseases (PGD, PGI or CGD) rather than the single-cause gill pathologies, such as AGD (Herrero et al, 2018;Gjessing et al, 2019;Laurin et al, 2019). So far, the extensive transcriptomic profiling of the gill tissue has been performed only in salmon exposed to the controlled environment of the closed-system tanks, following a single-pathogen challenge to induce either AGD (Morrison et al, 2006;Wynne et al, 2008a;Bloecher et al, 2018;Boison et al, 2019;Robledo et al, 2019) or infectious salmon anemia (Valenzuela-Miranda et al, 2015). In most cases, fish were subjected to a single-dose challenge of the infectious organisms, with only few studies evaluating the effects of re-infection (Bloecher et al, 2018;Boison et al, 2019) or co-exposure to other infectious agents, such as hydroids (Bloecher et al, 2018) and Yersinia ruckeri (Valdenegro-Vega et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the significance of the complement cascade in the host response to AGD remains unclear. However, a recent genome mapping study implicated the C4 gene as one of three genes involved in disease resistance in AGD [ 49 ], and genetic screening of susceptible versus resistant fish also demonstrated an upregulation of plasma protease C1 inhibitor in resistant gill samples [ 50 ]. Kube et al also demonstrated that resistance after one P. perurans infection was attributable to an innate response, in contrast to resistance after multiple infections [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…2019) and AGD (Robledo et al . 2020) have also successfully produced genome‐wide SNP chips suitable for research (Houston et al . 2014; Lien et al .…”
Section: History and Current Status Of Selective Breeding In The Ukmentioning
confidence: 99%
“…At the moment, genomic selection is the state of the art for salmon breeding (Table 3). Marker-assisted selection and genome-wide marker SNP array platforms have been used to improve salmon stock across several phenotypes (Zenger et al 2018) including disease resistance (Gonen et al 2015;Robledo et al 2016;Robledo et al 2019;Silva et al 2019;Rodr ıguez et al 2019;Robledo et al 2020), body size and weight (Reid et al 2005;Baranski et al 2010;Gutierrez et al 2012;Tsai et al 2015), but also delaying sexual maturation which can improve growth and meat quality (Pedersen et al 2013;Gutierrez et al 2014;Ayllon et al 2015;Barson et al 2015). As domestication of farmed Atlantic salmon progresses, genomic tools may also be used to assess impacts of the domestication process, examining the genetic basis for changes in growth, morphology, behaviour and physiology (Glover et al 2017;L opez et al 2019).…”
Section: State Of the Art In Breeding And Genomics Of Finfishmentioning
confidence: 99%
See 1 more Smart Citation